AKIBAT YURIDIS PERKAWINAN DIBAWAH TANGAN DALAM PRESPEKTIF HUKUM ISLAM DAN UNDANG-UNDANG PERKAWINAN - Gunadi (Program Studi Hukum Keluarga Islam, 2022)
Munawir Sjadzali's main concern lies in the premise that there are a number of verses of theQur'an, especially those relating to social issues, not rituals that are not in accordance withtoday's needs, such as inheritance law, slavery and bank interest. In this matter, Munawirrefers, among other things, to the spirit of caliph Umar bin Khattab's experience. This braveand honest pattern of ijtihad Umar bin Khattab has inspired Munawir to argue that theMuslim community should be honest and brave in dealing with Islamic law. Believing in thedynamics and vitality of shari'ah, he encouraged Muslims to actualize Islamic law.